2021
DOI: 10.1212/nxi.0000000000000977
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab-Induced Hypogammaglobulinemia and Infections in AQP4 and MOG Antibody–Associated Diseases

Abstract: ObjectiveTo determine the potential association between infections and rituximab (RTX)-induced hypogammaglobulinemia among patients with CNS inflammatory diseases.MethodsWe included in a prospective observational study all consecutive adults with aquaporin 4 (AQP4) or myelin oligodendrocyte glycoprotein (MOG) antibody–positive disorders treated with RTX. Dosing schedule was adapted to memory B-cell measurement.ResultsWe included 48 patients (mean age 47 [SD: 14] years; 77% females; 31 AQP4 positive and 17 MOG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 23 publications
3
30
3
Order By: Relevance
“…Several studies have shown that patients with MS or NMO-SD taking anti-CD20 have an increased risk of infection, 23 possibly related to hypogammaglobulinemia. 24 In our cohort, total IgG level tended to be associated with anti-S IgG titre and anti-SARS-CoV-2 Ig positivity. The postinfectious immune response has generally been poorly studied in patients with MS, contrarily to the postvaccination humoral response.…”
Section: Discussionmentioning
confidence: 47%
“…Several studies have shown that patients with MS or NMO-SD taking anti-CD20 have an increased risk of infection, 23 possibly related to hypogammaglobulinemia. 24 In our cohort, total IgG level tended to be associated with anti-S IgG titre and anti-SARS-CoV-2 Ig positivity. The postinfectious immune response has generally been poorly studied in patients with MS, contrarily to the postvaccination humoral response.…”
Section: Discussionmentioning
confidence: 47%
“… 13 , 14 Moreover, it may be reasonable in some patients (e.g., NMOSD with medical comorbidities and NMOSD with hypogammaglobulinemia) to consider tailoring their treatment regimen in hopes to minimize infectious risks. 15 …”
Section: Discussionmentioning
confidence: 99%
“…3 Treatment-induced hypogammaglobulinemia contributes to infections in patients with rheumatologic and hematologic diseases and neuromyelitis optica disorders treated with B-cell depleting therapy. [4][5][6] We do not know whether treatment-induced hypogammaglobulinemia could also be involved and be harmful in patients with MS (PwMS), who are generally younger and with fewer comorbidities than those with other diseases. Pivotal studies 1,7 have demonstrated that hypogammaglobulinemia is infrequent in PwMS during the first years of treatment, but little is known about its potential medium-term incidence in nonselected patients nor about its interaction with the risk of infection.…”
mentioning
confidence: 99%